MANAJEMEN DAKWAH DIGITAL DALAM PROSES PEMBELAJARAN DI ERA REVOLUSI INDUSTRI 4.0 - Yusuf, Erick; Sauri, Sofyan; Sukandar, Ahmad (Ar-Risalah: Media Keislaman, Pendidikan dan Hukum Islam, 2021)
Islamic character needs to be nurtured from an early age in overcoming the mounting cases of moral degradation. Educational institutions have a big role in fostering the character of students, one of which is the IHAQI Boarding School Bandung Creative Middle School, this school is one of the pesantren-based schools that was present in the era of the industrial revolution 4.0. This school applies digital da'wah in the learning process. This study used a qualitative approach with a case study method at IHAQI Boarding School Bandung Creative Junior High School. The results of the study illustrate that this pesantren has a unique learning management, namely applying digital da'wah in the learning process. At the planning stage, this digital da'wah is considered to have been carefully planned, it can be seen from the readiness of educators and students in applying digital programs during the learning process. At the implementation stage, this digital da'wah is felt to have been carried out effectively, seen by the existence of e-learning applications related to the learning process, Islamic mobile applications that can be accessed directly from cell phones and related to Islamic studies, as well as pictorial da'wah animations that have been made and designed by students in order to spread Islamic da'wah. As for the evaluation stage, this digital preaching has a positive impact in order to raise awareness to all students of the importance of spreading Islam and fostering Islamic values ​​in everyday life, and it needs to be improved more creatively, so that it is always updated, varied and more and more interesting.